2021
DOI: 10.1055/a-1362-9375
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of endoscopic esophageal findings for residual esophageal cancer after neoadjuvant chemoradiotherapy

Abstract: Background Endoscopic evaluation of the esophageal mucosa may play a role in an active surveillance strategy after neoadjuvant chemoradiotherapy (nCRT) for esophageal cancer. This study investigated the yield of endoscopic findings for detection of residual disease. Methods Patients from the multicenter preSANO cohort, who underwent nCRT followed by surgery for esophageal or junctional cancer, were included. Upper endoscopy was performed 6 and 12 weeks after nCRT. Patients with residual disease at 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Of 26 patients with residual cancer that remained undetected by bite-on-bite biopsies (i. e. with a false-negative biopsy outcome; 19 %), 22 (16 %) had a clinically complete response and underwent surgery because they were allocated to the standard surgery arm, three (2 %) had a positive FNA from a suspicious lymph node, and one (1 %) had a high suspicion of residual cancer on the basis of endoscopic and PET/CT findings [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Of 26 patients with residual cancer that remained undetected by bite-on-bite biopsies (i. e. with a false-negative biopsy outcome; 19 %), 22 (16 %) had a clinically complete response and underwent surgery because they were allocated to the standard surgery arm, three (2 %) had a positive FNA from a suspicious lymph node, and one (1 %) had a high suspicion of residual cancer on the basis of endoscopic and PET/CT findings [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this interval probably contained the most relevant information regarding the effects of radiotherapy-induced inflammation on dysphagia (that is dysphagia caused by swelling), as this inflammation is expected to resolve within the first year of active surveillance in patients with an ongoing cCR 19 . Furthermore, recent data have shown that 45 per cent of patients with stenosis early after nCRT and standard oesophagectomy have a complete response in the resection specimen 20 . For the subgroup of patients with such stenosis, it remains unknown whether the stenosis, with or without dysphagia, would have persisted if they had undergone active surveillance (with or without endoscopic dilatation) and remained cancer-free.…”
Section: Discussionmentioning
confidence: 99%
“…If cytology of suspicious lymph nodes is non-representative again, the patient should be considered to have residual disease and surgical resection is advised. Endoscopic suspicion of residual tumor after nCRT is associated with presence of residual disease (positive predictive value 91%) and further treatment of these patients should therefore be discussed in a multidisciplinary team [ 18 ].…”
Section: Methodsmentioning
confidence: 99%